2012
DOI: 10.1007/s10875-012-9681-4
|View full text |Cite
|
Sign up to set email alerts
|

IDO-Competent-DCs Induced by IFN-γ Attenuate Acute Rejection in rat Liver Transplantation

Abstract: Our results suggested that IDO gene expression correlates with the severity of acute rejection and that IFN-γ-induced IDO-positive DCs may attenuate acute rejection and catalyze local tryptophan metabolism via IDO enzyme expression, leading to immune tolerance after liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…By contrast, tumours at their late stage generate much more immunosuppressive factors, which impede the production of IFN-γ by T or NK cells. However, low levels of IFN-γ can stimulate immune cells such as macrophages and DCs to upregulate the expression of IDO1 and PD-L1 to mediate immunosuppression6162.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, tumours at their late stage generate much more immunosuppressive factors, which impede the production of IFN-γ by T or NK cells. However, low levels of IFN-γ can stimulate immune cells such as macrophages and DCs to upregulate the expression of IDO1 and PD-L1 to mediate immunosuppression6162.…”
Section: Discussionmentioning
confidence: 99%
“…However, the severe side effects of the current immunosuppressive drugs limits their application for the treatment of graft rejection. Recently, cell-mediated therapies have become more interesting with regard to the process of allograft rejection as well as their effectiveness in the induction and maintenance of immune tolerance [6,7]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, one promising way to overcome allograft rejection is the induction and maintenance of immune tolerance by cell-based therapies, such as dendritic cells (DCs) and T regulatory cells (Tregs) [6,7]. It is widely accepted that DCs act as the professional antigen-presenting cells to initiate immunity response by activation of native T cell response [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, exogenous IFN-γ prevented GVHD in a murine bone marrow transplantation model through post transplant inhibition of T cell proliferation (19, 20). IFN-γ stimulation of dendritic cells resulted in an upregulation of IDO production which mediated allograft protection in a rat liver transplantation model (21). Most relevant to our findings, a recent study by Garcia et al in a tolerant heart transplant model demonstrated that a monocytic suppressive cell population bearing the phenotype CD11b + Gr1 + CD115 + mediated their suppression via signaling responses to IFN-γ, as Ifngr -/- Gr1 + monocytes could not provide graft protection as wild-type Gr1 + cells did (10).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in transplantation have demonstrated that IFN-γ can be protective via a variety of mechanisms including mediating the suppressive function of MDSCs (10, 19-21). The potential sources of such IFN-γ are thought to be macrophages, T, NK and/or NKT cells, and can also result from phagocytosis of apoptotic cells in the spleen (22).…”
Section: Introductionmentioning
confidence: 99%